2012
DOI: 10.1016/j.ijgo.2012.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Gynecologic disorders and menstrual cycle lightheadedness in postural tachycardia syndrome

Abstract: Objective To assess differences in gynecologic history and lightheadedness during menstrual cycle phases among patients with POTS and healthy control women. Methods In a prospective, questionnaire‐based study carried out at Paden Autonomic Dysfunction Center, Vanderbilt University, between April 2005 and January 2009, a custom‐designed questionnaire was administered to patients with POTS (n = 65) and healthy individuals (n = 95). The results were analyzed via Fisher exact test and Mann–Whitney U test. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 24 publications
(28 reference statements)
0
29
2
Order By: Relevance
“…This stands in contrast to the Peggs et al [12] study in which female POTS patients reported a higher incidence of gynecological abnormalities like uterine bleeding, endometriosis, uterine fibroids, and ovarian cysts. This difference could be attributed to either different ratios of estrogen-to-progesterone or different levels of estradiol in VVS and POTS patients.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…This stands in contrast to the Peggs et al [12] study in which female POTS patients reported a higher incidence of gynecological abnormalities like uterine bleeding, endometriosis, uterine fibroids, and ovarian cysts. This difference could be attributed to either different ratios of estrogen-to-progesterone or different levels of estradiol in VVS and POTS patients.…”
Section: Discussioncontrasting
confidence: 87%
“…A recent study by Zesko et al showed that the results of tilt table tests are not affected by the phase of menstruation in premenopausal women[17]. In contrast to these data, a recent study by Peggs et al [12] showed that female POTS patients feel significantly more lightheaded during all phases of menstrual cycle compared to healthy subjects. The reason for POTS patients but not VVS patients feeling more lightheaded than healthy subjects may be due to an exaggerated sympathetic tone or more profound hypovolemia in POTS, which leads to increased tachycardia (a distinguishing feature of POTS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 80% of female patients report an exacerbation of symptoms around menstruation 5 . Many patients have been co-diagnosed with irritable bowel syndrome, some have hypermobile joints, and some have abnormal sudomotor regulation.…”
Section: Diagnostic Criteria and Common Clinical Features Of Potsmentioning
confidence: 99%
“…2 The POTS patient experiences symptoms caused by alterations in cerebral perfusion and activation of the sympathetic nervous system during upright postural changes. 8,9 The sum of symptoms has a large negative impact on quality of life. 1,[3][4][5][6][7] The clinical features of POTS vary between patients, and symptom severity can fluctuate in individuals on a daily or weekly basis.…”
mentioning
confidence: 99%